Novel MWCNT interconnected NiCo2O4 aerogels prepared by a supercritical CO2 drying method for ethanol electrooxidation in alkaline media - Jayaseelan, Santhana Sivabalan; Ko, Tae-Hoon; Radhakrishnan, S.; Yang, Cheol-Min; Kim, Hak-Yong; Kim, Byoung-Suhk (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The design and development of an economic and highly active non-precious electrocatalyst for ethanol electro-oxidation is challenging due to expensiveness of the precursors as well as processes and non-Eco friendliness. In this study, a novel preparation of mesoporous NiCo2O4-MWCNT nanocomposite aerogels based on sol gel technique is proposed. Multiwall carbon nanotube (MWCNT)-supported NiCo2O4 nanocomposite aerogels as an efficient catalyst for the ethanol electro-oxidation is reported. The MWCNTs exhibit an interconnected fibrous network with uniform dispersion of NiCo2O4 nanoparticles. The effects of MWCNT concentration on the ethanol electro-oxidation of MWCNT/NiCo2O4 aerogels are studied. We found that using a proper loading of MWCNTs allowed us to reach higher current densities for the oxidation of ethanol in an alkaline media. The highly porous and fibrous MWCNT/NiCo2O4 aerogels are the promising electro-catalysts for the oxidation of a direct ethanol fuel cell. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: REDUCED GRAPHENE OXIDE; ELECTROCHEMICAL OXIDATION; METHANOL; NANOPARTICLES; ELECTRODE; BEHAVIOR; NIO